Long noncoding RNA UPAT promotes colon tumorigenesis by inhibiting degradation of UHRF1 - Kenzui Taniue; Akiko Kurimoto; Hironobu Sugimasa; Emiko Nasu; Yasuko Takeda; Kei Iwasaki; Takeshi Nagashima; Mariko Okada; Masaaki Oyama; Hiroko Kozuka‐Hata; Masaya Hiyoshi; Joji Kitayama; et al. (2016)
Significance Many long noncoding RNAs (lncRNAs) play critical roles in tumor development. Here we show that an lncRNA termed UPAT [ubiquitin-like plant homeodomain and really interesting new gene finger domain-containing protein 1 (UHRF1) Protein Associated Transcript] is required for the tumorigenicity of colorectal cancer cells. UPAT interacts with and stabilizes the epigenetic factor UHRF1 by interfering with its ubiquitination and degradation. Furthermore, the UHRF1– UPAT axis up-regulates Stearoyl-CoA desaturase 1 and Sprouty 4 , which are required for the survival of colon tumor cells. Our study provides evidence for an lncRNA that regulates protein ubiquitination and degradation and thereby plays a critical role in the survival and tumorigenicity of tumor cells. Our results suggest that UPAT and UHRF1 may be promising molecular targets for the therapy of colon cancer.